1998
DOI: 10.1101/gad.12.17.2658
|View full text |Cite
|
Sign up to set email alerts
|

JNK targets p53 ubiquitination and degradation in nonstressed cells

Abstract: In this study we elucidated the role of nonactive JNK in regulating p53 stability. The amount of p53-JNK complex was inversely correlated with p53 level. A peptide corresponding to the JNK binding site on p53 efficiently blocked ubiquitination of p53. Similarly, p53 lacking the JNK binding site exhibits a longer half-life than p53 wt . Outcompeting JNK association with p53 increased the level of p53, whereas overexpression of a phosphorylation mutant form of JNK inhibited p53 accumulation. JNK-p53 and Mdm2-p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
267
1
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(285 citation statements)
references
References 33 publications
14
267
1
3
Order By: Relevance
“…Western blotting and JNK inhibition demonstrated that the constitutive JNK signal is required for SP1 expression. JNK pathway activation has been shown to play a role in the stability of transcription factors, which may also be the basis for the effect of JNK inhibition on SP1 expression seen in this study (55)(56)(57). Posttranslational modifications of SP1 have been implicated in the regulation of SP1 activity.…”
Section: Discussionmentioning
confidence: 54%
“…Western blotting and JNK inhibition demonstrated that the constitutive JNK signal is required for SP1 expression. JNK pathway activation has been shown to play a role in the stability of transcription factors, which may also be the basis for the effect of JNK inhibition on SP1 expression seen in this study (55)(56)(57). Posttranslational modifications of SP1 have been implicated in the regulation of SP1 activity.…”
Section: Discussionmentioning
confidence: 54%
“…105 JNK has also been found to form associations with p53 in nonstressed cells and it has been proposed to mediate p53 ubiquitination and degradation by forming an adaptor-molecule in the E3 ubiquitin-ligase complex. 106 This JNK-mediated degradation is MDM2-independent.…”
Section: Inhibition Of Mdm2-mediated Degradation Of P53 By Other Mechmentioning
confidence: 99%
“…As p53 ubiquitination was not completely abolished in extracts from MDM2-deficient cells, the existence of other molecules capable of targeting p53 for degradation was suggested. 125 Indeed, it was found that p53 can also be targeted for proteasomal degradation by three other E3-ubiquitin ligases namely Cop1, Pirh2 and synoviolin, from which the former two are regulated in a p53-dependent manner following IR. 36,37 Similar to the effects observed with increased MDM2 levels, overexpression of either Cop1 or Pirh2 resulted in the proteasomal destruction of p53 and concomitantly protected the cells from growth inhibition and apoptosis.…”
Section: P53-binding Proteinsmentioning
confidence: 99%